(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
Brachiopods are described from two horizons of the Bachu Formation from the Bachu area of the Tarim Basin, Xinjiang Province, northwest China. We assign the brachiopods from the basal Bachu Formation to late Famennian and correlate those from its upper part to the Eochoristites-Martiniella Assemblage of South China, of early Tournaisian age. The brachiopod fauna of the Bachu Formation exhibits strong generic and specific links with coeval South Chinese faunas, suggesting a close biogeographical affinity with the South China block. Eleven species are described, including one new species, Ptychomaletoechia bachuensis sp. nov.